Lest We Forget: An Estimate of Vikuosa Nienu's Contribution to the Archaeology of Northeast India. (25th June 2018) - Jamir, Tiatoshi
The present paper is the outcome of a small documentary research that the author undertook since the year 2009 on the early life and academic foundation of an archaeologist – Vikuosa Nienu, wherein his contribution to the archaeology of the region seem like an unfamiliar one to the majority of us from Northeast India. But the value of his work stands out for two reasons – firstly, prior to this research, no archaeological investigations had ever been conducted in Nagaland beyond mere archaeological reconnaissance. It was a time when political situations in Nagaland were tense, and field archaeology at that time was considered problematic and challenging. Secondly, this pioneering work is laudable because of its theoretical underpinnings of three dominant paradigms – culture-historical, processual and behavioural archaeology where Nienu gained exposure as a student at the University of California, Berkeley and at the Grasshopper Pueblo Field School during the early 1970s. The paper thus, examines Nienu's formative years at the School of Archaeology, New Delhi, and thereafter his field experiences, academic environment and the major paradigms that shaped his understanding of the region's prehistory in the course of his later research.